HUMANISTIC POTENTIAL OF "PHILOSOPHY OF COMMON CAUSE" OF N. FEDOROV - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article is devoted to the humanistic aspect of the cosmic philosophical doctrine of N. Fedorov analyzed in the context of secular humanism, which was formed in the 20th century and is still developing intensively. The aim of the article is to contrast the views of the thinker N. Fedorov with the key principles of secular humanism. The tasks are: – to determine the place of humanistic ideas of "Philosophy of the common case" in the heritage of the founder of cosmic philosophy – M. Fedorov; – to analyze the principles of modern humanism in the context of the issues of secular humanism, presented in the Humanist Manifestos; – to show the relevance of the ideas of M. Fedorov for the modern humanistic tradition. Research methods are: – a comparative method that enables to identify and compare the characteristic features of secular humanism and the active-evolutionary doctrine of M. Fedorov; – historical and cultural method is applied to restore the ideas of M. Fedorov through the prism of the main provisions of secular humanism; - principle of additionality is used to outline the meaningful provisions of the Humanist Manifestos as documents that reflect the normative-value system of modern time. Research results. M. Fedorov argues that evolutionary process is expected to be directed by human reason and morality dictate. The basis for the convergence of secular humanism and active Christianity of M. Fedorov is the theme of regulating natural processes based on the progress of science and technology at the consciously creative stage of the mankind’s evolution. Causing mortality by the spontaneity of the previous course of evolution, the thinker defends the idea of the immanent resurrection of all human generations as the ultimate and most important goal of the mankind’s existence. To M. Fedorov’s thought the search for immortality is the object of comprehensive scientific inquiry and the greatest reason for unification of people of the Earth, regardless of their nationality, race, citizenship or wealth. Achieving immortality for individuals alive today and future generations and resurrection of all people who ever lived are two inseparable goals, according to M. Fedorov. Discussion. The doctrine of M. Fedorov, the main provisions of which are: the resurrection of ancestors, the achievement of immortality, and the regulation of nature on a cosmic scale is not sufficiently investigated through the prism of modern theories of humanism. Conclusion. Active-evolutionary approach to the problem of death and immortality of man of M. Fedorov is in tune with the modern scientific quest, but it does not coincide with the main direction of secular humanism, which proves the feasibility of population decline